Employee Perceptions of Company Welfare Programs: A Qualitative Study in the Financial Sector - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This qualitative study explores employee perceptions of company welfare programs within Indonesia's financial sector, focusing on a private banking institution. Through in-depth interviews with 15 employees across various divisions, the research reveals that while health benefits and work flexibility are highly valued, significant disparities exist between policy design and practical implementation. Key challenges include bureaucratic access barriers, generational differences in benefit preferences, and inconsistent awareness of available programs. The findings emphasize that organizational culture, management support, and effective communication are pivotal in shaping employee experiences of welfare initiatives. The study contributes to human resource management literature by highlighting the need for more adaptive, employee-centric welfare strategies that address both structural and cultural dimensions of implementation. Practical implications suggest organizations must enhance program accessibility, tailor benefits to diverse workforce needs, and strengthen internal communication to maximize welfare program effectiveness.